SOME OBSERVATIONS ON THE SPERMATOZOA OF AQUARIUM FISHES - Rajagopal, S; Reddy, P Sitarami (Indian Journal of Fisheries, 2011)
The present paper deals with the morphology and biometry of the spermatozoa of four types of aquarium fishes viz., koi carp (Cyprinus carpb), black shark (Morulius chrysophakadion), marigold platy (Xiphophorus maculatus) and delta black guppy (Lebistes reticulatus) for the first time. The shape of the head, middle piece and tail have been described along with the biometric data. A comparative account of the spermatozoa of the four types of aquarium fishes has been incorporated